OSL dating of coastal dunes on the southeastern coast of Hainan Island, China - Zhou, Liang; Yang, Yang; Li, Gaocong; Tong, Changliang (Frontiers in Marine Science, 2023)
Coastal dune sediments and landforms offers a unique opportunity to understand the climate change and sea level change on the centennial-millennial time scale. However, there is a paucity of chronological studies on the effects of storms on the evolution of coastal dunes along the temperate coastline of China. In this study, optically stimulated luminescence (OSL) dating of sand dunes were conducted to investigate the process and mechanism of coastal dune evolution on the southeastern coast of Hainan Island, China. The results show that the costal dune evolution experienced three rapid accumulation periods: 28-21 ka, 14-4 ka, and 3.0 ka-present. The three rapid accumulation periods correspond to the last glacial maximum, the late Pleistocene/early-mid Holocene, and the late Holocene climatic dry-cold period, respectively. Sea level change, East Asian winter monsoon, and in conjunction with the enhanced storminess play a key role in driving the sand dune evolution on the south-eastern coast of Hainan Island. These findings are of great significance for regional planning and coastal defense schemes.